2015
DOI: 10.1016/j.jvsc.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Primary intra-aneurysmal surgical repair of a celiomesenteric trunk aneurysm

Abstract: We describe the surgical management of an asymptomatic 3-cm saccular aneurysm originating from a celiomesenteric trunk in a 45-year-old man. Surgical management was influenced by the location of the aneurysm, involving hepatic, splenic, and superior mesenteric arterial branches, by the young age of the patient, which made use of a synthetic graft less ideal, and by the lack of endovascular options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Visceral artery aneurysm is a rare disease, and the reported incidence is 0.1% to 0.2% of the population [ 1 , 2 ]. A CMT aneurysm is even rarer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visceral artery aneurysm is a rare disease, and the reported incidence is 0.1% to 0.2% of the population [ 1 , 2 ]. A CMT aneurysm is even rarer.…”
Section: Discussionmentioning
confidence: 99%
“…A CMT aneurysm is even rarer. A literature search revealed only 21 cases during the last 47 years [ 1 15 ], since Stanley et al [ 3 ] reported the first case treated by open repair. All the reported cases were treated by open surgical repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMT anatomic variations are rare; they have been reported to range between 1% and 2.7% of cases [ 8 ], whereas the incidence of visceral aneurysms ranges between 0.1% and 0.2% in the general population [ 9 ]. CMT aneurysm is even rarer and occurs in only 0.25% of all visceral artery anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Prior reports of patients with CMTs and aneurysmal or occlusive disease have focused on techniques of open or endovascular reconstructions, but none have described the use of fenestrated-branched endovascular aortic repair (FB-EVAR) for treatment of thoracoabdominal aortic aneurysms (TAAAs). [4][5][6][7][8][9][10] We report a patient who presented with a 7.9-cm TAAA affecting a CMT and was treated by FB-EVAR using double kissing directional branches for incorporation of the celiac axis (CA) and the superior mesenteric artery (SMA).…”
Section: Introductionmentioning
confidence: 99%